Money laundering : a new international law enforcement model - Stessens, Guy. (Cambridge [England] ; New York : Cambridge University Press, 2000)
"This book gives a broad analysis of the legal issues raised by the international fight against money laundering. It offers an extensive comparative research of the criminal and preventive law aspects from an international perspective. Guy Stessens portrays money laundering as a new criminal trend threatening both national and international societies which must be addressed multilaterally through banking practice, international conventions, and with respect for human rights.
Includes bibliographical references (p. 432-457) and index.
aia 19/8/16
Loans
Keywords: Money laundering --- Law and legislations; Money laundering; Money; International cooperation